Simulated patient training: Using inter-rater reliability to evaluate simulated patient consistency in nursing education - MacLean, Sharon; Geddes, Fiona; Kelly, Michelle; Della, Phillip (Churchill Livingstone, 2018)
© 2018 Background Simulated patients (SPs) are frequently used for training nursing students in communication skills. An acknowledged benefit of using SPs is the opportunity to provide a standardized approach by which participants can demonstrate and develop communication skills. However, relatively little evidence is available on how to best facilitate and evaluate the reliability and accuracy of SPs’ performances. Aim The aim of this study is to investigate the effectiveness of an evidenced based SP training framework to ensure standardization of SPs. The training framework was employed to improve inter-rater reliability of SPs. Methods A quasi-experimental study was employed to assess SP post-training understanding of simulation scenario parameters using inter-rater reliability agreement indices. Two phases of data collection took place. Initially a trial phase including audio-visual (AV) recordings of two undergraduate nursing students completing a simulation scenario is rated by eight SPs using the Interpersonal Communication Assessments Scale (ICAS) and Quality of Discharge Teaching Scale (QDTS). In phase 2, eight SP raters and four nursing faculty raters independently evaluated students’ (N = 42) communication practices using the QDTS. Results Intraclass correlation coefficients (ICC) were > 0.80 for both stages of the study in clinical communication skills. Conclusion The results support the premise that if trained appropriately, SPs have a high degree of reliability and validity to both facilitate and evaluate student performance in nurse education.